1998
DOI: 10.3354/ame016103
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance in Skagerrak-Kattegat coastal waters and host specificity of viruses infecting the marine photosynthetic flagellate Micromonas pusilla

Abstract: Seawater sampled in the Skagerrak and Kattegat coastal waters during the period October 1995 to September 1996 were screened for the occurrence of viruses lytic to marine microalgae.Viruses lytic to the photosynthetic marine picoflagellate Adicrornonas pusilla (Butcher) Manton & Parke (Prasinophyceae) were detected in all seawater samples screened Evidence for viral lysis of any other of the 11 algal species tested was not obtained. Several viruses infecting different strains of Ad, pusilla were isolated. Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 16 publications
3
47
0
Order By: Relevance
“…The host ranges of Micromonas pusilla virus (29), HaV (24), HaNIV (15), Heterosigma akashiwo RNA virus (34) and Emiliana huxleyi virus (31) are complex, and lysis by individual viral isolates was restricted to specific host strains. Because of the strain specificity, the importance of viruses in maintaining intraspecies diversity in algal populations is highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…The host ranges of Micromonas pusilla virus (29), HaV (24), HaNIV (15), Heterosigma akashiwo RNA virus (34) and Emiliana huxleyi virus (31) are complex, and lysis by individual viral isolates was restricted to specific host strains. Because of the strain specificity, the importance of viruses in maintaining intraspecies diversity in algal populations is highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…Strain-specificities of algal viruses have been reported in some host-virus systems, Heterosigma akashiwo-HaV (Nagasaki & Yamaguchi 1998), H. akashiwo-HaNIV (Lawrence et al 2001), and Micromonas pusilla-MpV (Sahlsten 1998). Tarutani et al (2000) reported that the majority of H. akashiwo cells surviving after bloom disintegration caused by viral infection were resistant to most simultaneously isolated HaV strains, and suggested that viral control of the clonal composition of H. akashiwo populations may occur in natural environments.…”
Section: Isolation Of Viruses and Their Host-rangementioning
confidence: 99%
“…MpV isolated from North Atlantic coastal water showed a diverse specificity to Micromonas pusilla strains isolated from different sites (Sahlsten 1998). Heterosigma akashiwo nucleic inclusion virus (HaNIV) isolated from British Columbia coastal water infected H. akashiwo strains isolated from the same area, but not those from other regions in the world (Lawrence et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, because only 1 H. akashiwo strain (H93616) was used by Tarutani et al (2000) to enumerate and isolate viruses, they presumably only enumerated and isolated viruses that were able to cause lysis of the given host strain (H93616), and viruses that did not lyse it, but lysed other H. akashiwo clone(s), were overlooked. Studies on cyanophages and Micromonas pusilla virus (MpV) have also shown that the viral titers estimated by means of the extinction dilution method using different host clones as hosts were variable (Waterbury & Valois 1993, Suttle & Chan 1994, Sahlsten 1998, Zingone et al 1999. Therefore, to fully examine the dynamics of algal viruses in environmental waters, use of multiple algal host strains with different virus sensitivity spectra is considered a rational way of minimizing any underestimation or overlooking of viruses.…”
Section: Introductionmentioning
confidence: 99%